Lo que no muere nunca Autobiografía de Takashi Pablo Nagai. - Vial, Elena (Humanitas (07172168))
The article focuses on the autobiography of Takashi Pablo Nagai, titled "What Never Dies," published in 2023. The work narrates the life of Nagai, a doctor and Christian who lived in Nagasaki, highlighting his conversion to Catholicism, his medical career, and his experience during the atomic bomb. Despite the sufferings he faced, including war and the loss of his wife, the narrative is characterized by an optimistic and humorous tone, reflecting his deep faith and commitment to peace. Additionally, it is mentioned that Takashi and his wife Midori are in the process of canonization, and the creation of an association in Italy to promote their beatification is highlighted.